1998
DOI: 10.1088/0953-8984/10/39/005
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of thiolate species formation on Cu(111) using soft x-ray photoelectron spectroscopy

Abstract: Soft x-ray photoelectron spectroscopy of the S 2p levels at relatively high spectral resolution has been used to characterize the interaction of methanethiol, , ethanethiol, and dimethyl disulphide, with a Cu(111) surface at temperatures from approximately 130 K to 500 K. The results are consistent with previous reports of the formation of a surface thiolate species at intermediate temperatures, but also provide clear evidence for two distinct surface intermediates in addition to the intact molecules and che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 24 publications
(42 reference statements)
4
36
1
Order By: Relevance
“…It is clear that an additional component is generated in proportion to increase of the temperature, which takes the position of the binding energy between atomic S and DMS. This middle state can be assigned to MT, and has been seen in studies of the dissociation of DMS on Rh(100) [9] and Cu(111) [8]. Figure 2 shows the corresponding C 1s XPS spectra for multilayer, submonolayer at 90, 130, 200 K and RT.…”
Section: Methodsmentioning
confidence: 59%
See 1 more Smart Citation
“…It is clear that an additional component is generated in proportion to increase of the temperature, which takes the position of the binding energy between atomic S and DMS. This middle state can be assigned to MT, and has been seen in studies of the dissociation of DMS on Rh(100) [9] and Cu(111) [8]. Figure 2 shows the corresponding C 1s XPS spectra for multilayer, submonolayer at 90, 130, 200 K and RT.…”
Section: Methodsmentioning
confidence: 59%
“…With regard to the highest temperature, this same state has been seen in atomic S/Rh(100) phase shown below the spectrum of RT phase. It is characterized by a binding energy significantly lower than that of any molecular states, which is investigated by many researches of the decomposition of sulfur-containing molecules on transition metal surfaces [8]. Therefore this component can be obviously identified as atomic S adsorption.…”
Section: Methodsmentioning
confidence: 99%
“…Studies of x-ray photoelectron spectroscopy have shown that C 2 H 5 SH decomposes to form C 2 H 5 S-on Cu(1 1 1) at 85 K and on Cu(1 1 0) at 100 K at lower coverages [5,11]. In Fig.…”
Section: Vibrational Studies Of Thermal Decomposition Of Hsch 2 Ch 2 Ohmentioning
confidence: 93%
“…On Cu(l 11) it was established some years ago that at room temperature methanethiol not only deprotonates to methanethiolate, CH3S-, but also causes a substantial reconstruction of the surface [15] which has recently been confirmed to involve a pseudo-square (lOO)-like surface layer of Cu atoms on the hexagonal layers of the underlying substrate [16]. S 2p SXPS characterization [17] has shown, however, that at low temperatures the intact thiol may coexist with a distinctly different thiolate species. It was suggested that this may correspond to adsorption on an unreconstructed surface, the reconstruction being kinetically hindered at low temperature.…”
Section: Surface Chemistry Of S-containing Moleculesmentioning
confidence: 99%